Modification of bioethanol production in an innovative pneumatic digester with non-thermal cold plasma detoxification. (April 2022) - Yoosefian, Seyedeh Hoda; Ebrahimi, Rahim; Hosseinzadeh Samani, Bahram; Maleki, Ali
Highlights: A novel anaerobic pneu-mechanical digester was designed. Ultrasound-acid pretreatment and hydrolysis applied and optimized. Cold plasma has detoxified biomass after hydrolysis. Anaerobic pneu-mechanical digester improved bioethanol production. Combination of cold plasma with pneumatic digester had well outcomes. Abstract: An anaerobic pneu-mechanical digester (PD) was designed to ferment lignocellulosic compounds. So, wheat and rice straws were pretreated using an ultrasound-acid, and then thermal-acid hydrolysis was conducted. Hydrolysis optimization was performed using the response surface method and the optimal points for time, temperature, and acid concentration were 45 min, 148.4 °C, and 2.04 % v/v, respectively. Cold plasma was then used as detoxification to reduce the amount of inhibitory compounds and acids. This method was capable of reducing the amounts of acetic acid, formic acid and furfural by 73, 83 and 68 % in hydrolyzed biomass, respectively. The biomass was fermented in a PD for 20 days and compared with a conventional digester (CD). The obtained results showed that the PD could increase the efficiency of bioethanol by 37 % in the detoxified state and 22 % in the non-detoxified state after 20 days of fermentation compared to the CD. Moreover, H2 S, CO and O2 were measured during fermentation process. In PD, the amount of H2 S and O2 was lower than CD, but CO was significantly higher in the PD.